THE SELECTION OF EFFICIENT SHARIA STOCKS FOR THE FORMATION OF AN OPTIMAL PORTFOLIO - Taufik Nugroho; Aam Slamet Rusydiana (Universitas Airlangga, 2020)
The analysis of the optimal portfolio allows investors to analyze appropriate to minimize the risks accepted by the objective of maximizing profit with the same risk among existing stocks. Data Envelopment Analysis (DEA) is used to determine the stocks with efficient performance based on ratio analysis. Having selected some stocks, the efficient formation of the optimal portfolio is then performed with a single index models and determined how much the proportion of funds invested in each stock. The sample data used are stocks in listed ISSI 2012-2016. Based on the analysis of efficiency as a candidate portfolio models using DEA - CCR and DEA – BCC, it generate 16 efficient stocks that form the candidate portfolio. After the analysis of all 16 efficient stock, it obtained 6 stocks to form the optimal portfolio Keywords: Optimal Portfolio, DEA, Stocks Efficiency, Single Index ModelREFFERENCE Adler N and B Golany. (2001). Evaluation of deregulated airline networks using data envelopment analysis combined with principal component analysis with an application to western europe. EJOR, 132(2), 260-273.Banker, R.D., Charnes, A., and Cooper, W.W. (1984). Some models for estimating technical and `scale inefficiency in data envelopment analysis. Management Science, 30 (9), 1078-92. Brigham, F. Eugene and Philip R. Daves. (2004). Intermediate Financial Management, eighth edition. New York: McGraw-Hill, Inc.Brigham, E.F. and Houston, J.F. (2007). Fundamentals of financial management. London: Thomson. Bursa Efek Indonesia. (2015). Data factbook Bursa Efek Indonesia tahun 2015. Jakarta: Bursa Efek Indonesia. Bursa Efek Indonesia. (2015). Data Statistik Bursa Efek Indonesia tahun 2015. Jakarta: Bursa Efek Indonesia.Charnes, A., Cooper, W.W., and Rhodes, E. (1978). Measuring the efficiency of decision making units. European Journal of Operation Research, 2(6), 429- 44. Chen, Hsin-Hung. (2008). Stock selection using data envelopment analysis. Industrial Management & Data Systems, 108(9), 1255-1268. Elton, Edwin J, Martin J, Gruber, and Manfred W. Padberg. (1976). Simple criteria for optimal portfolio selection. The Journal of Finance, 31(5), 296-302.Elton Edwin J., and Martin J. Gruber. (1995). Risk reduction and portfolio size: An analytical solution. Journal of Business, 50(4), 415-437.Elton, Edwin J and Martim J Gruber. (1995). Modern portofolio theory and insturement analysis, Fith Edition. Toronto: John Willey & Sons, Inc.Hartono, Jogiyanto. (2010). Teori portofolio dan analisis investasi. Yogyakarta; BPFE.Leila Zamazami et al,. (2014). Portfolio selecton using data envelopment analysis (DEA): A case of selected indi invesment companies. International journal of current research and academic review, 2(4), 50-55.Leivo, Timo, H. & Patari, Eero J. (2010). Ehancement of Value Portfolio Performance Using Data Envelopment Analysis. Studie in Economics and Finance, 27(3), 223-246.Werastuti, Desak Nyoman Sri. (2014). Pembentukan Portofolio Optimal melalui Pendekatan Efisiensi. Jurnal Ilmiah Akuntansi dan Humanika, 3(4), 1262-1289.